The Interplay Between Money Attitudes, Financial Management Behaviour and Financial Well‑Being: The Moderator Effect of Financial Risk Tolerance - Swarmilah Hariani; Swarmilah Hariani; A Fakhrorazi; Rusdi Omar; Hafiz Abdul Samee Malik; Apollo Daito (Business, Management & Accounting Journal (BISMA), 2026)
This study investigates the relationship between attitudes toward money, financial management behaviour, and financial well-being among both public and private sector lecturers in Indonesia. The aim is to understand how individuals' perceptions and attitudes toward money influence their financial management practices and, consequently, their overall financial well-being. Data were collected through a survey administered to 393 respondents, and the analysis underscores the significance of financial literacy and sound financial management behaviour. The findings reveal that attitudes toward money have a substantial and positive effect on financial management behaviour. Furthermore, financial management behaviour was found to significantly contribute to enhancing individuals' financial well-being. The study also identified attitudes toward money as an intervening variable that strengthens the relationship between financial management behaviour and financial well-being. Conversely, financial risk tolerance was not found to be a moderating factor in the relationships between attitudes toward money and financial well-being, nor between financial management behaviour and financial well-being. These results highlight the critical importance of a comprehensive understanding of attitudes toward money to better inform strategies aimed at improving individual financial management and overall financial well-being.